A study on the factors that influence urban and rural voters choice in 13th general election / Ahmad Zulhilmi Ahmad Hizam and Muhammad Amirul Naim Ibrahim - Ahmad Hizam, Ahmad Zulhilmi; Muhammad Amirul Naim, Ibrahim (2013)
In 13th General Election, Barisan Nasional only won 133 parliamentary seat and record slightly reduced performance in 2008 but managed to wrest Kedah from Pakatan Rakyat, meanwhile Pakatan Rakyat won 89 seat show the increasing performance and maintain their rule in Selangor and Penang (Razak Ahmad & A. Samy, 2013). There is a altering of vote of preference among the urban and middle class of Malaysia whereby it shows that urban area more likely to choose opposition party while in rural area the voter prefer to the government. So, this study focus on the factor that influence the urban and rural voter choice. To get the information, the researcher distribute the questionnaires towards the total of 282 respondents in urban area which is Sungai Petani and rural area which is Merbok. In this research, cluster sampling design and census sampling technique will be used to select the sample. Furthermore, the expected findings of the study for the factor that most influence the urban and rural voter choice in Malaysia 13th General Election for the urban area is the social identity while for the rural area is political issue. It is recommended for the voters to vote because voting right is the privilege toward the citizen to choose the government so the voter should register to vote to fulfil their responsibility toward the country to choose the government and their representative at the parliament and state assembly. Besides, the researcher recommended to the future researcher to do the research in different parliamentary or state assembly in order to know more about the factor of urban and rural voter choice.